2022
DOI: 10.3389/fmars.2022.977719
|View full text |Cite
|
Sign up to set email alerts
|

The gene expression profile of the glucocorticoid receptor 1 (gr1) but not gr2 is modulated in mucosal tissues of gilthead sea bream (Sparus aurata) exposed to acute air-exposure stress

Abstract: The perception of an acute stressor (short-duration; high-intensity) induces a physiological response that activates the hypothalamic-pituitary-interrenal (HPI) axis and the subsequent release of cortisol. Cortisol carries out its effect at the molecular level through its recognition by the mineralocorticoid receptor (MR) and the glucocorticoid receptor (GR). Recently, we unveiled the nucleotide sequence of the glucocorticoid receptor 1 (gr1) and gr2 in gilthead sea bream (Sparus aurata). Importantly, GR1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In the particular context of gilthead sea bream, it remains to elucidate the effect of the stress response upon the modulation of the gr1 and gr2 at the gene expression level. In this context, a recent study revealed that in mucosal tissues gr1 but not gr2 is modulated in gilthead sea bream exposed to acute airexposure stress (Vallejos-Vidal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the particular context of gilthead sea bream, it remains to elucidate the effect of the stress response upon the modulation of the gr1 and gr2 at the gene expression level. In this context, a recent study revealed that in mucosal tissues gr1 but not gr2 is modulated in gilthead sea bream exposed to acute airexposure stress (Vallejos-Vidal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the dynamic of the response, the evaluation of more time points in the experimental design will provide a clearer perspective on expression dynamics at dorsal and ventral lesions, particularly of those markers that, in our study, only showed downregulation or an increased trend (but not significant). In this way, the analysis of the activation of the stress response and transcriptional activity at earlier times (i.e., 1-, 6-, and 24-hours post-injury as a measure to evaluate the immediate effect of the stimulus [ 4 , 62 , 63 ]) will shed light on the mode of action orchestrated by different systems to ensure tissue repair, defense, and protection of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Although beneficial for short term stress response, long-term upregulation may sequester energy from other essential functions (e.g., growth, reproduction, osmoregulation) (Kennedy and Janz 2023). The degree to which cortisol levels (and subsequent upregulation of Glucocorticoid Receptor 1) can vary widely between fish species (Vallejos-Vidal et al 2022), and quantification of stress based on expression requires specific previous knowledge on species and population (Aedo et al 2023). Given that no baseline is currently known for the Sandusky River spawning population, the important distinction in our study is that Glucocorticoid Receptor 1 expression was found to be consistent both across time periods (pre and post sampling) and across treatment groups (gill biopsy and combined treatment).…”
Section: Discussionmentioning
confidence: 99%
“…2021) that has evaluated the stress response in fish using expression of Glucocorticoid Receptor 1 has indicated that short-term stressors (e.g., air exposure, handling) result in increased expression or GR1 in a time and tissue dependent manner. Although this may be specific to individual species, generally GR1 expression is found to decrease within 24 hours of exposure to the stressor (Vallejos-Vidal et al 2022). In the case of chronic stress, however, GR1 expression remains elevated for longer durations (days to weeks; Tort 2011).…”
Section: Tablesmentioning
confidence: 99%
See 1 more Smart Citation